Исследование возможности группового управления роботами - Швачко, П. М. (ХНУРЭ, 2012)
This work is devoted the study of possibility of group management robots. Robots are used in many areas of science, technique and industry especially where the vital functions of man are laboured or in general impossible. There fore there is a row of problems at group application of robots. It is a problem of organization of cooperation of robots in groups at the decision of intricate having a special purpose problem and problem of communication, related to organization of cooperation of robots.
Keywords: групповое управление роботами; роботы